EVALUASI E-SERVICE (STUDI KASUS: E-LAYANAN BADAN KEPEGAWAIAN DAERAH PROVINSI SUMATERA SELATAN) - Ria Aprinda; Widya Cholil (Jurnal Ilmiah Matrik, 2023)
Abstract: This research is based on efforts to improve the quality of government electronic-based services at the Regional Civil Service Agency of South Sumatra Province through website evaluation (e-service). The study was conducted using Kepmenpan-RB No. 859/2019 on seven instruments/dimensions, namely efficiency, trust, convenience, reliability, service, availability of information, and interaction. The method used is Mix-Method. The population data in this study was obtained from the Civil Service Information System of South Sumatra. The number of samples used was 100 respondents using the Slovin formula. Data dissemination using questionnaires to users (ASNs). By using the SPSS 25 tool, validity test results are obtained that state the data is valid. As for the reliability test, cronbach α > 0.70 so it was declared good. From the results of the distribution of respondents' answers, it was found that the index of the e-Service website is in good value.